(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
People’s need for a safe place to deposit money led to the development of commercial banking. It didn’t require a lot of investment for the individuals who held others’ overflow cash to understand that their business could be made productive assuming they loan out again what was gotten by them, given that it was returned when it was required. The banking business is comprised of borrowing and lending, which are the bank’s two primary functions. The modern banker performs numerous other duties in addition to these two fundamental ones. The following are the roles that commercial banks play namely Accepting Deposits, Advancing Loans, and Other Services.